Belinsky I. D. Verbalization of spirituality in the cycle «Songs of innocence» by William Blake - Belinsky I. D. (Philological Treatises, 2020)
The article is devoted to William Blake’s ways of verbalization of his spiritual searches declared in «Songs of Innocence» according to his philosophical and esthetic views; general description of linguistic units is carried out through the system of tropes and the means of their expression are identified